Conducting Plate’s Eddy-Current Losses - Andriušienė, L.; Degutis, A.; Kostrauskas, P.; Mikalajūnas, D. (Elektronika ir Elektrotechnika, 2004)
It is assumed that all electromagnetic processes vary in a harmonic way in the laminated corner of the transformer’s magneticsystem.It is proved that due to technological air-gaps existing in the laminated corners of power transformers’ magnetic systems,additional eddy-currents originate which are distributed unevenly because of the skin-effect. Ellipticity of eddy-currents contours isstated. Presuming that the magnetic flux densities both in the centre and periphery of the magnetic system’s corner are known,differential equations for the distribution of magnetic field are obtained. On the basis of the solved differential equations the activelosses of eddy-currents are calculated, which depend on the square of magnetic flux densities in the centre and periphery of the corner,the thickness of plate, dimensions of the corner, specific resistance and the square of frequency. Methods are proposed for theminimization of eddy-currents active losses by reducing the permeability in the central zone of the magnetic system’s corner or by usingthe elementary zones for the discretization of the magnetic system’s corner zone. Ill. 3, bibl. 2 (in English; summaries in Lithuanian,English, Russian).